Early Glycine Supplementation Re-Establishes Adrenal Catecholamine Secretion in Hypothalamic Obesity Model in Rats but does not Affect Visceral Adiposity. - Eliza Andreazzi Ana; Augusto da Silva Silvioney; Silva Chaves Alexandre; da Silveira Goulart Guimarães Ernesto; Grossi Pettersen Klaus; Sacramento Silva Marcos; Schaeffer Fontoura Tamiris; Tavares Paes Santiago; Alberto Mourão Júnior Carlos; Cezar de Freitas Mathias Paulo; Marcel González Garcia Raúl (Journal of Glycomics And Metabolism, 2015)
Obesity is a worldwide epidemic that features a multifactorial syndrome characterized by a chronic positive energetic unbalance. Neonatal administration of monosodium L-glutamate (MSG) causes lesion on the arcuate nucleus of hypothalamus that led to development of obesity in the adult life in rodents characterized by a notorious accumulation of catecholamine in the adrenal medulla. The amino acid glycine induces catecholamine secretion of adrenal medulla. Thus, the objective of our work was to evaluate the possible effects of glycine administration in the MSG-obesity model in rats and investigate its impact on adrenal catecholamine medulla homeostasis. Male Wistar rats received MSG solution (4mg/g body weight) subcutaneously in the cervical area for 5 days after delivery, controls received saline solution. Animals were also divided in two groups, in which one received tap water added with glycine (0.1g/Kg) after weaning on 21st day until 90 days of life.Biometrical variables, visceral fat pads weight, total content and basal secretion of adrenal cathecolamine were evaluated. Glycine increased Lee index of all tested groups and had no effect on visceral adiposity. However, glycine treatment completely reestablished catecholamine total content and basal secretion of MSG-obese group. In conclusion, although glycine treatment apparently completely reestablishes catecholamine secretion homeostasis it is not sufficient to significant directly reduce visceral adiposity in MSG obesity model in rats.
Keywords: Glycine